Visionary Leadership and Vision Achievement in Higher Education: The Mediating Role of Lecturers' Organizational Commitment - Wiwin Widyati; Saiful Anwar; Ichwani Siti Utami; Ubaid Al Faruq; Shella Rachmawaty (Educazione: Journal of Education and Learning, 2026)
Large universities often struggle to convert visionary leadership into tangible institutional achievement, particularly when bureaucratic inertia and a heterogeneous lecturer population fragment a shared sense of purpose. This study examines the mediating role of lecturers' organizational commitment in linking visionary leadership to the acceleration of higher education vision achievement. An explanatory quantitative approach was employed, drawing on a sample of 335 permanent lecturers at a large private university selected through proportional random sampling. Data were collected through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4, evaluating both the measurement and structural models through a bootstrapping procedure. The findings reveal that visionary leadership influences vision achievement directly (0.350) and, more strongly, by shaping organizational commitment (0.493), which in turn drives vision achievement (0.220). The significant indirect effect (0.108; t = 3.724) confirms partial mediation, and the model explains 51.2 percent of the variance in vision achievement. The implication for transformational education and learning is that committed lecturers are the carriers of educational change, translating institutional vision into classroom practice. Strengthening leadership and lecturer commitment together therefore offers a sustainable pathway toward durable, learning-centered transformation in higher education.